Condições brasileiras que impactam a implementação de modelos de gestão importados - Araújo Filho, Edmundo Bueno de (2001)
This article analyzes the competitivity on knowledge society, also considered apostcapitalist, post-modern society. Under that perspective, knowledge is the most valuable asset. The one, however, that is subordinated to each persons desire to acquire it and apply it. Trying to achieve more competitivity, organizations from developed countries create administration models that are imported by less developed societies as way to extend their own leveis of productitivity. However this does not guarantee that these models will besuccessfully applied because of local cultural and social-economical aspects. In Brazil, such aspects stimulate the importation of these administration models. However, these models does not work as expected and does not produze the aimed results. We try to demonstrate these Brazilian conditions on theoretical and applied levei is demonstrated using a representative study of case showing a well-succeeded importation that has been stimulated by the same Brazilian conditions.